Antimicrobial potential and cytotoxicity of silver nanoparticles phytosynthesized by pomegranate peel extract - Fernandes, Renan Aparecido [UNESP]; Berretta, Andresa Aparecida; Torres, Elina Cassia; Buszinski, Andrei Felipe Moreira; Fernandes, Gabriela Lopes [UNESP]; Mendes-Gouvêa, Carla Corrêa [UNESP]; De Souza-Neto, Francisco Nunes; Gorup, Luiz Fernando; De Camargo, Emerson Rodrigues; Barbosa, Debora Barros [UNESP] (MDPI, 2018)
The phytosynthesis of metal nanoparticles is nowadays attracting the increased attention of researchers and is much needed given the worldwide matter related to environmental contamination. The antimicrobial activity of colloidal and spray formulation of silver nanoparticles (AgNPs) synthesized by pomegranate peel extract against Candida albicans and Staphylococcus aureus, and their cytotoxicity in mammalian cells were tested in the present study. Dry matter, pH, total phenolics, and ellagic acid in the extract were determined. Then, AgNPs were phytosynthesized and characterized by X-ray diffraction, electron transmission microscopy, dynamic light scattering, zeta potential, and Ag+ dosage. Spray formulations and respective chemical-AgNP controls were prepared and tested. The peel extract reduced more than 99% of Ag+, and produced nanoparticles with irregular forms and an 89-nm mean size. All AgNP presented antimicrobial activity, and the spray formulation of green-AgNP increased by 255 and 4 times the effectiveness against S. aureus and C. albicans, respectively. The cytotoxicity of colloidal and spray green-AgNP was expressively lower than the respective chemical controls. Pomegranate peel extract produced stable AgNP with antimicrobial action and low cytotoxicity, stimulating its use in the biomedical field.
Keywords: Candida albicans; Herbal medicine; Nanoparticles; Punicaceae; Silver; Staphylococcus aureus